2020
DOI: 10.1080/15438627.2020.1723099
|View full text |Cite
|
Sign up to set email alerts
|

Males with chronic ankle instability demonstrate deficits in neurocognitive function compared to control and copers

Abstract: The purpose of this study was to determine if there were neurocognitive deficits among controls, copers and those with chronic ankle instability (CAI). Participants included those without history of ankle injury (n = 14), ankle sprain copers (n = 13) and patients with self-reported CAI (n = 14). They completed a battery of valid and reliable computer-based neurocognitive tests. The differences between neurocognitive domain scores were compared across the Control, Coper and CAI groups. Patients with CAI had low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, while Rosen et al [9] reported lower cognitive scores related to memory and simple attention in males with CAI, a deficit in executive function (a domain that likely plays an essential role in sensorimotor integration) was not found. It should also be noted that although some of the reported cognitive scores among CAI were lower than controls, they did not reach a level necessary to classify the CAI subjects as having a cognitive impairment [9]. It is possible that dual-task motor and cognitive functions tend to deteriorate in both assignments in individuals with CAI, since complex motor tasks might be very cognitively demanding compared to the control.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Furthermore, while Rosen et al [9] reported lower cognitive scores related to memory and simple attention in males with CAI, a deficit in executive function (a domain that likely plays an essential role in sensorimotor integration) was not found. It should also be noted that although some of the reported cognitive scores among CAI were lower than controls, they did not reach a level necessary to classify the CAI subjects as having a cognitive impairment [9]. It is possible that dual-task motor and cognitive functions tend to deteriorate in both assignments in individuals with CAI, since complex motor tasks might be very cognitively demanding compared to the control.…”
Section: Discussionmentioning
confidence: 85%
“…Based on studies that tested dual-task performance, it was suggested that deficits in central neural sensorimotor integration contribute to impaired movement control in people with CAI [3][4][5]. However, very few studies tested cognitive function separately from movement in subjects with CAI [8][9][10], and only one study used a full battery of neurocognitive tests [9]. The present study included a diverse sample of subjects with CAI, both in gender and in level of physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, there is evidence to support that neurocognitive function is altered following joint injury, such as ACL injury and chronic ankle instability. 46,212,219 For example, patients with ACLR who exhibited worse visual cognition scores demonstrated greater proprioceptive errors and greater time to stability during single-leg landing. 220 Neurophysiologic evidence supports greater demands on brain regions associated with neurocognitive function during simple motor tasks after ACLR compared with healthy controls, 46,212 suggesting that patients require greater attentional and cognitive processing to perform motor and proprioceptive tasks after ACLR.…”
Section: Emerging Interventionsmentioning
confidence: 99%